Complete chloroplast genome sequence of Convolvulus arvensis. Issue 7 (3rd July 2021) - Wang, Zhiqiang; Song, Hui; Jiang, Dechun
Abstract: The complete chloroplast genome of Convolvulus arvensis was reconstructed by reference-based assembly using Illumina paired-end data. The assembled plastome is 153, 234 base pairs (bp) in length, including a pair of inverted repeat regions (IRs) of 22, 662 bp each, a large single-copy region (LSC) of 89, 059 bp and a small single-copy region (SSC) of 19, 651 bp. A total of 115 genes were predicted from the chloroplast genome, including 74 protein coding genes, 37 tRNA genes and 4 rRNA genes. The overall GC content of C. arvensis chloroplast genome was 37.7%. Phylogenetic analysis with several reported chloroplast genomes showed that C. arvensis is closely clustered with Operculina macrocarpa . The complete chloroplast genome of C. arvensis provides new insight into the evolutionary and genomic studies of Convolvulaceae.